PUSTAKAWAN, MEDIA SOSIAL DAN INFORMASI HOAX: MENYOAL PERAN PUSTAKAWAN SEBAGAI PENJAGA INFORMASI (INFORMATION GATE KEEPER) - Yunus Winoto (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2019)
The development of technology in a society is unavoidable. One of the evidences of the development of information technology (IT) is the increasing use of social media in society. Social media facilitate people to convey their ideas, thoughts, information and to disseminate them to others without selection. However, one of the effects of social media is the uncontrollable spread of hoaxes in the midst of society. One of the tasks of librarians in the library activities is to select information sources or, in other words, to be the information gate keeper. In the broader context, the task of librarians is not only to select materials in the library but also to provide knowledge, understanding and skills to public in receiving, selecting and using good, correct and useful information. Therefore, information and media literacy and knowledge and skills in using information technology are prerequisites or must- have skills for today’s librarians.